Integrating Technology-Enhanced Communicative Language Teaching in EFL Contexts: A Mixed-Methods Analysis of Student Engagement and Language Proficiency Outcomes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the effectiveness of integrating technology-enhanced communicative language teaching (TECLT) methods in English as a Foreign Language (EFL) university contexts. Using a mixed-methods approach with 120 upper-intermediate EFL learners over one academic semester, the research investigates how combining traditional communicative approaches with digital tools affects student engagement, motivation, and language proficiency outcomes. Quantitative data from pre- and post-tests, along with qualitative data from student interviews and classroom observations, reveal significant improvements in speaking fluency, interactive competence, and learner autonomy. The findings suggest that strategic integration of technology within a communicative framework addresses longstanding challenges in EFL teaching, particularly in contexts where target language exposure remains limited outside classroom settings. This study contributes to ongoing discussions about effective pedagogy in language education by demonstrating that technology serves not as a replacement but as an amplifier of communicative principles when implemented with clear pedagogical objectives.